ANALYSIS OF FACTORS AFFECTING THE ONLINE PAYMENT SERVICE USAGE BEHAVIOR OF STUDENTS AT HO CHI MINH CITY UNIVERSITY OF AGRICULTURE AND FORESTRY - Quoc Tran Minh; Qui Nguyen Anh; Tien Nguyen Thi Ai; Hoa Ha Thi Thu; Ly Tran Dinh (HUIT Journal of Science, 2025)
This study was conducted to identify the factors affecting the behavior of using online payment services (OPS) and to demonstrate the extent to which these factors influence the OPS usage behavior of students at Ho Chi Minh City University of Agriculture and Forestry (HCMUAF). The data analysis methods applied in this study include descriptive statistics, reliability assessment of the measurement scale (Cronbach’s Alpha), exploratory factor analysis (EFA), and multiple regression analysis. The results indicate that there are six factors influencing OPS usage behavior in decreasing order of impact as follows: Perceived Usefulness (HI), Ease of Use (SD), Security (BM), Facilitating Conditions (TL), Risk (RR), and Social Influence (AH). Among these, the Risk factor negatively affects the behavior of using online payment services. In addition, the study also proposes several solutions for service providers such as improving and developing payment applications; enhancing cybersecurity and network safety; and increasing the organization of seminars and programs to attract more partners and potential customers, thereby contributing to the enhancement and promotion of online payment service usage behavior.